2021
DOI: 10.2147/opth.s298700
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapy & Age in Choroidal Cancers: A Retrospective Cohort Analysis of 7722 Patients from a US National Database

Abstract: Background Collectively, choroidal cancers represent a vast array of histopathologically diverse constituencies with profound repercussions related to mortality and metastasis. Prognosticated factors provide utility in determining clinical management and outcome propensities. To date, measures to collectively characterize choroidal cancers as a class are not impressive. This study aims to shed light on the affiliation of age and therapeutic modalities to survival in patients diagnosed with choroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(73 reference statements)
0
1
0
Order By: Relevance
“… 38 The cohort analysis conducted by Hussain et al showed that compared with patients who did not receive chemotherapy, chemotherapy significantly affected the survival rate of patients with choroidal cancer (HR = 0.377, 95% CI 0.292–0.486, p < 0.001). 39 Moreover, an Asian retrospective study of 12 patients with CM reported that 66.7% of patients achieved CM regression when treated with chemotherapy alone. 24 Further, studies have reported that the combination of chemotherapy with intravenous bevacizumab may also be effective in cases of intraocular metastases.…”
Section: Management Optionsmentioning
confidence: 99%
“… 38 The cohort analysis conducted by Hussain et al showed that compared with patients who did not receive chemotherapy, chemotherapy significantly affected the survival rate of patients with choroidal cancer (HR = 0.377, 95% CI 0.292–0.486, p < 0.001). 39 Moreover, an Asian retrospective study of 12 patients with CM reported that 66.7% of patients achieved CM regression when treated with chemotherapy alone. 24 Further, studies have reported that the combination of chemotherapy with intravenous bevacizumab may also be effective in cases of intraocular metastases.…”
Section: Management Optionsmentioning
confidence: 99%